Approaches to Managing Herniated Disc Surgical vs. Conservative Treatment - Banyś, Filip; Wiak, Iga; Bochen, Konrad; Czyżewski, Filip; Dziegciarczyk, Anna; Górska, Weronika; Jasiński, Filip; Łukawski, Artur; Szałajska, Julia; Wojtach, Klaudia (Quality in Sport, 2024)
Introduction Disc herniation is a displacement of an intervertebral disc, most often caused by degeneration of its outer layer, the annulus fibrosus. This condition can cause various symptoms such as numbness, pain, muscle weakness or lose of sensation. While many patients can be successfully treated with non-surgical methods, some of them some require surgical intervention. Aim of study The objective of this study is to evaluate both surgical and non-surgical treatment methods for herniated disc and seeks to introduce doctors and patients to the advantages and disadvantages associated with them. State of Knowledge Disk herniation occurs when disk material prolapses beyond intervertebral disk’s space. The symptoms may arise when displaced material start to compress major structures located nearby, such as spinal nerves. The most common causes include age-related degeneration, repetitive movements, obesity, trauma or genetic predisposition. Summary (Conclusion) Disk herniation can be managed with various non-surgical and surgical methods. Conservative treatment should be considered as first line treatment showing high success rate for mild to moderate cases in long term relief and preventing recurrence of symptoms. Surgical options offer better short-term relief for sever and more advanced cases but carry greater risks of side effects and involve longer recovery time. Best approach should be carefully selected based on the severity of symptoms and patient needs.